OPIOID-DEPENDENT MOTHERS IN MEDICAL DECISION MAKING ABOUT THEIR INFANTS’ TREATMENT: WHO IS VULNERABLE AND WHY? - UUSITALO, SUSANNE; AXELIN, ANNA (Les ateliers de l'éthique / The Ethics Forum, 2017)
Infants born to opioid-dependent women are typically admitted to neonatal intensive-care units for management of neonatal abstinence syndrome (NAS), and their treatment requires medical decision making. It is not only the infants’ vulnerability, in terms of their incompetence and medical condition, that is present in those circumstances, but also the mothers’ situational vulnerability, which arises with the possibility of their engagement in medical decision making regarding their infants. Vulnerability is a concept that has often, if not always, been traced back to individuals. In this paper, we suggest that in some cases evaluations and attributions of vulnerability to either individuals or populations fall short of capturing all aspects of vulnerability. We ask whether this individual-based evaluation is sufficient for identifying all the vulnerabilities arising in the situation. Moreover, we suggest that the “unit” of vulnerability attribution, typically a person who is a likely target of harm and/or moral violations, should not simply be reduced to the individual. Rather, the unit should in some cases be seen as constituted by an entity that is interpersonal in nature. The kind of real vulnerability that we identify in this paper is inherently embedded in a dyadic relationship, and notions of vulnerability that decompose social relations into individuals run the risk of missing the vulnerability in question. We elaborate this kind vulnerability by discussing of role of opioid-dependent mothers in decision making about their infants’ treatment.